2018
DOI: 10.3389/fphys.2018.00531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Muscle Function and Limb Loading Asymmetries on Gait and Balance in People With Multiple Sclerosis

Abstract: People with MS (PwMS) often have a more- and less-affected side of the body which results in a variety of asymmetries, including measures of power, strength, muscle activity, and limb loading. Though many studies have identified asymmetries, their impact on gait and balance in PwMS is currently unclear. In this mini-review we first summarize previous findings of asymmetries in muscle function and limb loading and their impact on gait and balance in PwMS. We then provide potential explanations for this lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
(51 reference statements)
1
21
1
Order By: Relevance
“…An interesting aspect is the study of the degree of symmetry in the lower limbs, as often the disease does not affect both sides of the body equally [45], and PwMS most often present asymmetry in force between limb [17,18,[46][47][48][49], and some studies have found that the degree of asymmetry is inversely related to walking ability [24,32,47]. The lower-limb explained a 20-30% of the variance functional capacity tests between PwMS, which is the reason why muscle training is recommended to minimize strength asymmetry between limbs [46], although other studies have not corroborated this association [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting aspect is the study of the degree of symmetry in the lower limbs, as often the disease does not affect both sides of the body equally [45], and PwMS most often present asymmetry in force between limb [17,18,[46][47][48][49], and some studies have found that the degree of asymmetry is inversely related to walking ability [24,32,47]. The lower-limb explained a 20-30% of the variance functional capacity tests between PwMS, which is the reason why muscle training is recommended to minimize strength asymmetry between limbs [46], although other studies have not corroborated this association [50].…”
Section: Discussionmentioning
confidence: 99%
“…The studies that have been carried out on symmetry in PwMS have been of a transverse type, so we can only analyze the association of asymmetry with other disease parameters, physiological or functional; longitudinal studies are needed to explain the causal factors of asymmetry, including studies with more standardized methodologies and protocols [18]. For potential use by health or physical activity professionals caring for PwMS, for the variables analyzed in this study we showed reference values with points of separation between quartiles, grouped by type of MS and degree of neurological disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current review aimed to summarize studies examining the efficacy of exercise training on asymmetry in physical fitness, physical function, and gait in persons diagnosed with either MS, PD, or having experienced an ischemic stroke. These conditions were selected given the presence of reported asymmetries in function within these groups (Djaldetti et al, 2006;Lauziere et al, 2014;Rudroff and Proessl, 2018). Exercise training was defined as any "planned structured and repetitive bodily movement done to improve or maintain one or more components of physical fitness" (Bouchard et al, 1994).…”
Section: Article Inclusion Criteria and Search Strategymentioning
confidence: 99%
“…In persons with CNCs, impairments in body functions often present in an asymmetrical pattern, creating a significant difference between contralateral limbs and muscle groups (Rudroff and Proessl, 2018), often described as an "affected" and "non-affected" limb (Sun et al, 2018). Indeed, asymmetries have been observed for temporal and spatial gait outcomes, limb loading, and muscular strength and power in these populations (Djaldetti et al, 2006;Lauziere et al, 2014;Rudroff and Proessl, 2018).…”
Section: Introductionmentioning
confidence: 99%